Le protesi di gomito: considerazioni cliniche e metodologiche - Moscolo, A.; Micheloni, G.; Mazzi, M.; Giaretta, S. (Lo Scalpello - Journal, 2019)
ELBOW ARTHROPLASTY: CLINICAL AND METHODOLOGIES CONSIDERATIONS Elbow replacement has been typically used for patients suffering from autoimmune arthritis resistant to medical therapy; at present, some of its main indications are chronic degenerative diseases, like primary osteoarthritis, and further distal humerus fractures, not otherwise synthesized, in selected cases. They are classified as total arthroplasty or partial arthroplasty (the latter recommended in younger patients in the absence of joint instability); and as constrained or unconstrained prostheses (more frequently implanted and characterised by kinematic patterns more similar to normal); regardless of the indication, a 5-year survival rate between 72 and 84% is reported. It is essential to verify the joint stability, if necessary, pursuing a careful reconstruction/reinsertion of the ligamentous and myotendinous apparatus, an accurate implant cementation to prevent possible aseptic complications. Elbow replacement is routinely used in its variants in patients often affected by various comorbidities and therefore more exposed to mechanical or infectious complications. Even with results which are still not comparable to THR or TKR, elbow replacement can be considered an interesting systemcharacterised by rather fast recovery times and good results in terms of pain relief and functional improvement. The complexity of the surgical technique and the still limited numbers of implants suggest to centralise this pathology in reference centres.